Modeling of X‐ray photoelectron spectra: surface and core hole effects1. (15th January 2014) - Pauly, Nicolas; Tougaard, Sven; Yubero, Francisco; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The shape and intensity of photoelectron peaks are strongly affected by extrinsic excitations due to electron transport out of the surface and by intrinsic excitations induced by the sudden creation of the static core hole. Besides, elastic electron scattering may also be important. These effects should be included in the theoretical description of the emitted photoelectron peaks. To investigate the importance of surface and core hole effects relative to elastic scattering effect, we have calculated full XPS spectra for the Cu 2p emissions of Cu and CuO with the simulation of electron spectra for surface analysis (SESSA) software and with a convolution procedure using the differential inelastic electron scattering cross‐section obtained with the quantitative analysis of electron energy loss in XPS (QUEELS‐XPS) software. Surface and core hole effects are included in QUEELS‐XPS but absent in SESSA while elastic electron scattering effects are included in SESSA but absent in QUEELS‐XPS. Our results show that the shape of the XPS spectra are strongly modified because of surface and core hole effects, especially for energy losses smaller than about 20 eV. Copyright © 2014 John Wiley & Sons, Ltd.